Analisis Nilai Toleransi Dalam Buku Bahasa Indonesia Kurikulum Merdeka Sekolah Dasar - Ngulya, Khilyatul; Sukardi, Sukardi (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
Developing students’ positive character is important, particularly the character of tolerance to minimize cases of intolerance. This study aims to describe the form of tolerance learning contained in the Indonesian language book of the independent curriculum for grade II elementary school. The formulation of the problem is how the form of tolerance learning is contained in the Indonesian language book of the Merdeka Curriculum for Grade II Elementary School. This research is library research. Data collection techniques using reading techniques, note-taking techniques, and documentation. The data collection instrument is a human instrument. The data analysis technique uses content analysis techniques. The object of this research is the Indonesian language book for the independent curriculum for grade II elementary school by Widjati Hartiningtyas & Eni Priyanti entitled